Magnetic Properties and Coercivity of MnGa Films Deposited on Different Substrates. Issue 3 (March 2017) - Feng, J.N.; Liu, W.; Gong, W.J.; Zhao, X.G.; Kim, D.; Choi, C.J.; Zhang, Z.D.
Abstract : MnGa films were grown by magnetron sputtering on thermally oxidized Si (Si/SiO2 ) and glass substrates. Films grown on single-crystal Si (100) substrate with different underlayers were prepared for comparison. It is found that the Si/SiO2 substrate is more suitable for growing high-coercivity MnGa films than the glass substrate, which is the result of the isolated-island-like growth. A coercivity of 9.7 kOe can be achieved for the 10 nm MnGa films grown on Si/SiO2 substrate at substrate temperature T S of 450 °C. Optimized experimental conditions are specified by changing the thickness of the MnGa films and the temperature of the substrates.